The holobiont concept before Margulis. Issue 3 (10th February 2020) - Baedke, Jan; Fábregas‐Tejeda, Alejandro; Nieves Delgado, Abigail
Abstract: In recent years, Lynn Margulis has been credited in various articles as the person who introduced the concept of holobiont into biology in the early 1990s. Today, the origin of evolutionary studies on holobionts is closely linked to her name. However, Margulis was not the first person to use this concept in its current context. That honor goes to the German theoretical biologist Adolf Meyer‐Abich, who introduced the holobiont concept nearly 50 years before her (in 1943). Although nearly completely forgotten today, in the 1940–60s he developed a comprehensive theory of evolutionary change through "holobiosis." It had a surprisingly modern outlook, as it not only addressed tenets of today's evolutionary developmental biology (evo‐devo), like the origin of form and production of variation, but also anticipated key elements of Margulis' later endosymbiotic theory. As the holobiont concept has become an important guiding concept for organizing research, labeling conferences, and publishing articles on host‐microbiota collectives and hologenomes, the field should become aware of the independent origin of this concept in the context of holistic biology of the 1940s. Abstract : The evolution of endosymbiotic theory and the holobiont concept. The conventional historical narrative states that Lynn Margulis introduced the "holobiont" concept. We show that German theoretical biologist Adolf Meyer‐Abich developed an earlier, comprehensive theory of holobionts in the 1940–60s. Research Highlights: The conventional historical narrative states that Lynn Margulis introduced the holobiont concept. In this paper, we show that German theoretical biologist Adolf Meyer‐Abich developed an earlier, comprehensive theory of holobionts in the 1940–60s.